Therapeutic aerosols in children. Issue 6898 (24th July 1993) - Thomas, S H; Batchelor, S; O'Doherty, M J
Abstract : The use and variety of drugs administered to children as inhaled aerosols is increasing, but little is known about how much drug reaches the lung and how it is distributed there in different age groups. In this article the reasons for measuring aerosol deposition in children are discussed and the potential methods for doing this described. Of the methods available, only the use of radiolabelled aerosols gives accurate information on total lung deposition and distribution. The potential risk of the radiation exposure required for these measurements varies with the age of the child but seems to be small. Properly designed studies are expected to clarify the factors affecting lung deposition in children and identify methods of inhalation associated with efficient and predictable delivery of the drug. Measurements of radioaerosol deposition may therefore be justified in children when this information is expected to lead to improvements in the effectiveness or safety of their treatment.